2018
DOI: 10.3390/economies6040056
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Governance Quality on Economic Growth: Based on China’s Provincial Panel Data

Abstract: This paper investigates the impact of governance quality on economic growth in China. After developing a theoretical framework for the effect of governance quality on local economic growth, this article studies the panel data in provincial regions over the period 2001–2015 by constructing a new comprehensive index of provincial governance, and checks the robustness of the empirical findings from four aspects. The results show that governance quality has a positive effect on economic growth, due to good governa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
31
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 30 publications
6
31
0
4
Order By: Relevance
“…The economic environment must improve significantly for entrepreneurs to make a meaningful impact in the region. Fayissa and Nsiah (2013), Liu et al (2018) found a significant positive correlation between the quality of governance and economic growth. While high-quality governance enhances economic growth in developed economy, it has no significant impact on low-income economies and region.…”
Section: Theoretical Underpinning and Literature Reviewmentioning
confidence: 90%
“…The economic environment must improve significantly for entrepreneurs to make a meaningful impact in the region. Fayissa and Nsiah (2013), Liu et al (2018) found a significant positive correlation between the quality of governance and economic growth. While high-quality governance enhances economic growth in developed economy, it has no significant impact on low-income economies and region.…”
Section: Theoretical Underpinning and Literature Reviewmentioning
confidence: 90%
“…Moreover, the study shows that the most wanted/desirable investments by local authorities from the Romanian rural area (namely those in local roads) have no impact on LED and the difference of LED between the commune that invested (through non-refundable program) in local roads and those communes that did not invest decreased over time. Thus, we would recommend extra-diligence when deciding how to invest limited public financial resources [58], following a strategic approach [59], especially in the context of financial crises [60] or underperforming local revenue mobilization [61]; we also need to take into account the relationship between good/quality governance and growth [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Economic growth is the dependent variable of this research, and some past studies used the indicator Gross Domestic Product per capita (Barro, 1991;Liu et al, 2018), whereas some studies used the growth rate of Gross Domestic Product as a measure of growth. However, sub-national per capita GDP (Gross County Product (GCP)) growth rate data are available for Kenyan counties, 2014-2017, resulting in the study to adopt per capita county GDP in final estimation.…”
Section: Measurement Of Variables and Sources Of Datamentioning
confidence: 99%